Effect of the p53 P72R Polymorphism on Mutant TP53 Allele Selection in Human Cancer. (8th February 2021) - De Souza, Cristabelle; Madden, Jill; Koestler, Devin C; Minn, Dennis; Montoya, Dennis J; Minn, Kay; Raetz, Alan G; Zhu, Zheng; Xiao, Wen-Wu; Tahmassebi, Neeki; Reddy, Harikumara; Nelson, Nina; et al.
Abstract: Background: TP53 mutations occur in more than 50% of cancers. We sought to determine the effect of the intragenic P72R single nucleotide polymorphism (SNP; rs1042522 ) on the oncogenic properties of mutant p53. Methods: P72R allelic selection in tumors was determined from genotype calls and a Gaussian distributed mixture model. The SNP effect on mutant p53 was determined in p53-negative cancer cell lines. RNA-sequencing, chromatin immunoprecipitation, and survival analysis were performed to describe the SNP effect. All statistical tests were 2-sided. Results: Among 409 patients with germline heterozygous P72R SNP who harbored somatic mutations in  TP53, we observed a selection bias against missense  TP53  mutants encoding the P72 SNP ( P  = 1.64 x 10 -13 ). Exogenously expressed hotspot p53 mutants with the P72 SNP were negatively selected in cancer cells. Gene expression analyses showed the enrichment of p53 pathway genes and inflammatory genes in cancer cells transduced with mutants encoding P72 SNP. Immune gene signature is enriched in patients harboring missense TP53 mutations with homozygous P72 SNP. These patients have improved overall survival as compared with those with the R72 SNP ( P  = .04). Conclusion: This is the largest study demonstrating a selection against the P72 SNP. Missense p53 mutants with the P72 SNP retain partial wild-type tumor-suppressive functions, which may explain the selection bias against P72 SNP across cancer types. Ovarian cancer patients with the P72 SNP have a better prognosis than with the R72 SNP. Our study describes a previously unknown role through which the  rs1042522  SNP modifies tumor suppressor activities of mutant p53 in patients.